Особливості методики викладання української мови як іноземної - Андрея Певсе; Andreya Pevse; Pősze Andrea (Szegedi Tudományegyetem Szláv Filológiai Tanszéke, 2021)
Abstract. Today, society needs a teacher who is competent, motivated, ICT-literate, capable of professional reflection, open to changes and innovations in the educational process, and is ready to help students develop life skills. Our country, like other countries of the world, has come to the conclusion that it is necessary to form a person who speaks not only his/her native language, but also many others, which indicates his/her multicultural orientation. There is a lot of research by both Ukrainian and foreign linguists on the basic methods of teaching foreign languages. They all have both positive and negative characteristics. However, all linguists agree that in order to achieve results, we must use different methods.

Резюме. Україна все ширше відкриває простори для іноземних громадян до пізнання і вивчення її культури, історії, літератури й мови. Викладачі-філологи намагаються розробити методику, розраховану на швидке, ефективне, різноманітне та цікаве навчання української як іноземної.
Keywords: módszer; differenciált oktatás; nyelvoktatás; different methods; methods; linguists foreing languages